Navigating liver toxicity in the age of novel oncological agentsKey points - Mar Riveiro-Barciela; Eleonora De Martin (JHEP Reports)
Summary: The advent of novel oncological therapies, including immune checkpoint inhibitors, antibody-drug conjugates, and protein kinase inhibitors, has revolutionised cancer treatment by significantly improving patient survival across a range of malignancies. However, these advances have been accompanied by the emergence of new and often unpredictable adverse events, among which hepatotoxicity represents a growing clinical challenge. In this review, we provide a comprehensive synthesis of current knowledge on liver injury associated with these three key classes of oncological agents, with a particular focus on mechanisms of action and hepatotoxicity, clinical presentation, and management strategies. Given the expanding use of these agents, both as monotherapies or in combination regimens, this topic is of pressing relevance to hepatologists and oncologists alike. As combination therapies become increasingly common, the complexity of drug–liver interactions and their implications for patient safety demand greater interdisciplinary awareness and collaboration. This review advocates for a pragmatic approach to the management of drug-induced liver injury in patients with cancer, underscoring the critical need to balance hepatic preservation with the imperative of maintaining oncological efficacy in this uniquely vulnerable population. By addressing an emerging area of clinical importance, we aim to stimulate further research on oncological hepatotoxicity, a phenomenon that is poised to become increasingly prevalent in routine clinical practice.